Eminent domain destroys a community: leveling East Arlington to make way for the Pentagon. Issue 1 (2nd January 2016) - Perry, Nancy
Abstract : This study examines the eminent domain action in 1942 where the federal government took 411 acres of land, including an African American neighborhood, to construct the Pentagon building in Arlington County, Virginia. The Fifth Amendment of the U.S. Constitution acknowledges the right of the federal government to exercise eminent domain where needed for the common good, but requires that property owners be given just compensation. This study explores the issue of compensation: what the residents lost when they were forced to move, how that loss was compensated, and whether the compensation was "just." The study data include interviews with former residents of the neighborhood, oral histories, land records, census data, photographs, and newspaper articles. The study concludes that the federal government compensated the residents for land and buildings, but was unable to compensate for a lost community. For many residents, that community is mourned even 72 years later.